Subacute Canine Monocytic Ehrlichiosis in a Two Month Old Siberian-Husky Puppy – Diagnosis and Therapeutic Management - Subramanian, Saravanan; Ganapathy, Selvaraju (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Canine monocytic ehrlichiosis (CME) caused by E. canis is most pathogenic and transmitted by the tick vector Riphicephalus sanguineus with non-regenerative anaemia and thrombocytopenia as common haematological abnormalities (Piratae et al., 2019). The disease may progress as acute, subacute and chronic, and in acute form, fever, anorexia, ocular discharge, petechiae, epistaxis, pale mucosae, bleeding signs, lymphadenopathy, and neurological signs may be observed (Waner and Harrus, 2013). In chronic phase, severe pancytopenia due to bone marrow hypoplasia is characteristic, which leads to severe leukopenia, anaemia, and thrombocytopenia resulting in death (Angkanaporn et al., 2022). Usually, the detection of E. canis (morulae) in dogs by conventional microscopy becomes very difficult owing to the low parasitaemia (Singh et al., 2021) and thus failure of detection in an early stage leads to chronic myelosuppressive form, which is often fatal. Siberian husky is the breed highly susceptible to CME, however, the incidence in this breed is rarely reported in India (Singh et al., 2021). This study reports an early diagnosis of sub-acute ehrlichiosis in a Siberian husky puppy and it’s successful therapeutic management.